(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background:Thyroid lesions are fairly common worldwide and are commonly encountered in clinical practice. The incidence of various thyroid disorders shows a striking variation; both, on a national and regional basis. Thyroid gland can be affected by a wide spectrum of diseases ranging from functional and immunologically mediated enlargement to neoplastic lesions. Objective:This study was carried out to estimate the frequency of thyroid lesions with respect to histopathological types and to correlate thyroid lesions with demographic data and clinical features.Materials and Methods: This study included all types of thyroid specimens received in the department of Pathology; AMC MET Medical College, Ahmedabad from June 2019 to December 2020. Results:Among the total 40 cases of thyroid lesions studied, the non-neoplastic lesions accounted for 26 cases (65%) and the neoplastic lesions constituted 14 cases (35%). The most common non-neoplastic lesion was multinodular /adenomatoid goiter (50%), followed by Hashimoto thyroiditis (7.5%), thyroglossal duct cyst (5%) and diffuse hyperplasia (2.5%). The most common benign neoplasm was Follicular adenoma (7.5%) and the most common malignant neoplasm was papillary carcinoma (17.5%). Two cases (5%) of Non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) of low / unknown malignant potential were reported.Conclusion: Histopathological examination of thyroid lesions provides definite diagnosis; which is mandatory for further management of patient.